FDI Inflows vs. Domestic Private Investment Stagnation : Investigating Crowding-In or Crowding-Out Effects - Kavya Diwakar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Foreign Direct Investment (FDI) is often championed as a catalyst for economic growth in developing and emerging economies. However, concerns persist that burgeoning FDI inflows might inadvertently stifle domestic private investment (DPI) – a phenomenon known as "crowding out." Conversely, FDI could stimulate DPI through "crowding in" effects like technology spillovers and market expansion. This research paper investigates the complex relationship between FDI and DPI, seeking to answer the critical question: Does increasing FDI lead to crowding out or crowding in of domestic private investment? Utilizing a comprehensive theoretical framework, review of empirical literature, and proposed methodological approaches, the paper finds the relationship is highly context-dependent. Key factors include the type of FDI, host country characteristics (financial market depth, institutional quality, human capital, sector), and macroeconomic stability. The paper concludes with nuanced policy implications, emphasizing that maximizing the positive impact of FDI on domestic investment requires targeted strategies beyond simply attracting capital.
Keywords: Foreign Direct Investment (FDI); Domestic Private Investment (DPI); Crowding Out; Crowding In Investment Stagnation; Resource Competition; Market Stealing-Competition